F. A. Hayek vs. J. M. Keynes in Shackle's marginal gloss*. Issue 2 (4th March 2018) - Repapis, Constantinos
ABSTRACT: The intellectual rivalry of F. A. Hayek and J. M. Keynes has recently caught the attention of historians of economic thought, journalists and the broad public. However, how was it viewed at the time? This article uses archival material in the form of marginal annotations made by G. L. S. Shackle to determine contemporary reading responses to the theoretical developments of the 1930s. Shackle's unique reading style that includes legible, dated, annotations and the fact that a substantial part of his academic library survives gives us a unique vantage point from which to explore anew this period of intellectual history.